An automated system for cattle reproductive management under the IoT framework. Part II: Induction of luteinizing hormone release after gonadotropin releasing hormone analogue delivery with e-Synch - Ren, Yue; Duhatschek, Douglas; Bartolomeu, C. C.; Laplacette, Ana L.; Perez, Martin M.; Rial, Clara; Erickson, David; Giordano, Julio O. (Frontiers in Animal Science, 2023)
Technologies for automating animal management and monitoring tasks can improve efficiency and productivity of livestock production. We developed the e-Synch system for automated control and monitoring the estrous cycle of cattle through intravaginal hormone delivery and sensing. Thus, our objective was to evaluate luteinizing hormone (LH) concentrations after intravaginal instillation of the Gonadotropin-releasing hormone (GnRH) analogue Gonadorelin with the e-Synch. This system consists of an intravaginal electronically controlled automated hormone delivery and sensing device integrated with an IoT platform. Lactating Holsteins with their estrous cycle synchronized were used in two experiments (Exp). In Exp1, at 48 h after induction of luteolysis, cows (n=5-6\group) were randomized to receive 100µg of Gonadorelin through intramuscular (i.m.) injection, 100µg of Gonadorelin in a 2 mL solution delivered with e-Synch, and an empty e-Synch device. In Exp2, at 48 h after induction of luteolysis cows (n=6-7\group) were randomized to receive 100µg of Gonadorelin i.m., or an intravaginal treatment with e-Synch consisting of 100 or 1,000µg of Gonadorelin in 2 or 10mL of solution containing 10% citric acid as absorption enhancer. Circulating concentrations of LH were analyzed with linear mixed models with or without repeated measurements. In Exp1, cows in the i.m. Gonadorelin treatment had a surge of LH whereas cows in the other two treatments did not have a surge of LH for up to 8 h after treatment. In Exp2, the 1,000µg dose of Gonadorelin elicited more LH release than the 100µg dose, regardless of solution quantity. The overall LH response as determined by area under the curve, mean, and maximum LH concentrations was similar between cows receiving 1,000µg of Gonadorelin delivered with e-Synch and 100 μg of Gonadorelin i.m. Increasing volume of solution for delivering the same dose of Gonadorelin partially increased LH release only for the 100 µg dose. We conclude that the e-Synch system could be used to automatically release Gonadorelin in a dose and volume that induces a surge of LH of similar magnitude than after i.m. injection of 100 μg of Gonadorelin. Also, the dose of Gonadorelin delivered by e-Synch is more critical than the volume of solution used.